Vergemeinschaftung und Distinktion Eine gesprächsanalytische Studie über Positionierungspraktiken in Diskussionen über TV-Serien - Weiser-Zurmühlen, Kristin (Reihe Germanistische Linguistik, 2021)
One of the reasons for the social significance of pop-cultural formats like TV series is how they are communicatively processed in interactions. This book uses video recordings of conversations between students about series to develop an analytical model that allows researchers to investigate community-forming activities and knowledge construction, and to relate them to the media and aesthetic resources of series for practices of positioning.